Impact of Relationship Marketing on Customer Retention in Higher Education - Shrestha, Sajeeb Kumar (Management Dynamics, 2020)
This research attempts to measure the impact of relationship marketing on customer retention in higher education. Exploratory cum descriptive and causal research design was used. Sources of data are students, parents, and faculties of different colleges. A convenient sampling method was used for sample selection. Structured questionnaires were used for collecting responses. Primary cross-section data were collected. PLS-SEM was used for testing the psychometric and econometric properties of the model. This research confirmed that relationship marketing, customer orientation, customer satisfaction, and customer retention are possible in the academic sector. Policymakers and academic experts should focus on relationship marketing factors and customer orientation to enhance customer satisfaction and customer retention.